Risk assessment of combined occupational exposure to hexavalent chromium, nickel, and PAHs: a literature-based approach - Tavares, Ana Maria (2021)
Occupational exposure is usually characterized by a complex mixture of chemicals, originating from different raw materials and transformation processes. Co-exposure to hexavalent chromium (Cr(VI)), nickel (Ni) and polycyclic aromatic hydrocarbons (PAHs) can occur in some workplaces. These substances display well-known genotoxic and carcinogenic effects, especially in the respiratory tract, sharing similar modes of action. However, reference values for occupational exposure only account for individual components exposure and not for a potential mixture effect. In the scope of HBM4EU Initiative, we performed a mixtures risk assessment (MRA) based on literature from occupational studies conducted in the European Union that contain human biomonitoring (HBM) data on Cr(VI), Ni and/or PAHs. After HBM data extraction, Hazard Quotient (HQ) and Hazard Index (HI) were calculated for binary and tertiary mixtures. Exposure was considered of concern if HI>1. Twenty-four articles were selected, most (n=18, 75%) presenting Cr(VI) and Ni exposure biomarkers. Among these, HI>1 was obtained for all studies on welding activities, in which chromium was the main driver of toxicity with HQ>1 in most measurements. Only two studies in waste incineration setting reported exposure to the three substances, and again all HI>1. Noteworthy, for some of the analysed studies, although exposure levels were below the reference values, still the mixture was considered of concern (HI>1). Our findings show the limitations of applying occupational exposure reference values defined on a single substance basis to workplaces, highlighting the relevance of MRA as a more realistic approach to provide more suitable risk management measures in occupational settings.